Pengembangan Media Interaktif Canva Berbasis PBL untuk Meningkatkan Kemampuan Literasi Numerasi Matematis Siswa SMP: Development of PBL-Based Interactive Canva Media to Enhance Mathematical Numeracy Literacy Skills of Junior High School Students - Popy Sigalingging; Dian Armanto; Edy Surya (ITScience (Information Technology and Science), 2026)
Mathematical numeracy literacy is an essential competency for students; however, assessment results and preliminary research indicate that the numeracy literacy skills of students at SMP Negeri 2 Kualuh Selatan remain very low. This issue necessitates instructional innovation through the use of digital media and interactive learning models to facilitate meaningful conceptual understanding. This study employs the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The research was conducted at SMP Negeri 2 Kualuh Selatan with 30 eighth-grade students as subjects. Data collection techniques included interviews, questionnaires, tests, and observations. Data analysis was performed using both descriptive qualitative and quantitative methods. The results of this development research indicate that: validity tests placed the media in the